Structural Changes In Amyloplast During Storage Of Bioprimed Corh 4 Rice Hybrid (Applied Biological Research, 2016)
In all cereal grains, starch is synthesized and stored in the form of granules in amyloplast. In rice  endosperm each amyloplast contains more than one starch granule. The rice amyloplasts produce  compound granules comprising of several dozen polyhedral, sharp-edged and easily separable  granules (Mares et al., 2002). The polyhedral shape of rice starch is due to the compression of  starch granules during seed development. Seed priming is controlled hydration of seed which  permit all metabolic activities to occur inside the seed but restricts the actual radicle protrusion  (Farooq et al., 2005). In biopriming, the seed are hydrated in bioagent solution and the bioagent  may be a biofertilizer or a biocontrol agent (Nayaka et al., 2010). Pseudomonas fluorescens is a  biocontrol agent involved in plant growth promoting activities and control of pathogenic infection.
Keywords: Structural; Amyloplast; Bioprimed